The relationship of interest in majors and confidence with students' career planning - Fitri Ningsih; Daharnis Daharnis (International Journal of Applied Counseling and Social Sciences, 2021)
One of the factors that influence career planning is interest in majors and self-confidence. This study aims to analyze the relationship between interest in majors and self-confidence with career planning. Methods This research uses a descriptive correlational quantitative method. The research population was the XI grade students of SMK Negeri 3 Padang as many as 246 students and the research sample amounted to 153 students. Sampling using proportional random sampling technique. The instrument used is a Likert Scale model. The research data were analyzed by simple regression and multiple regression. The results of this study indicate that, in general, interest in majors is in the high category, self-confidence is in the high category, student career planning is in the high category, there is a significant relationship between interest in majors and student career planning, there is a significant relationship between trust There is a significant relationship between interest in majors and self-confidence with students' career planning.